OC-023 Specialist Care of in-Patients with Non-Variceal upper Gastrointestinal Bleeding is Associated with a Dramatically Shorter Length of Stay. (4th June 2013) - Venkatachalapathy, S V; Grasso, N; Chung-faye, G; Dubois, P; Forgacs, I; Logan, R P; Hayee, B
Abstract : Introduction: Acute upper gastrointestinal bleeding (UGIB) is a common medical emergency that has a 10% mortality rate [1], requiring specialist input and management [2]. It is not known if the care, outcome and length of stay of UGIB is influenced by whether patients are primarily cared for by Gastroenterologists or General physicians. We conducted a retrospective study to assess these aspects of care for in-patients with UGIB. Methods: A retrospective review of case-notes (Electronic patient record-EPR) was conducted for all patients admitted to Kings College hospital with suspected UGIB between February and September 2012. Patients were divided as to whether they came immediately under the care of Gastroenterologists (GI) or general physicians (non-GI) after initial evaluation in the Acute Admission Unit. Patients were assigned on the basis of bed availability in a ward-based system. Statistical comparisons were made as appropriate with t-test or Fisher's exact test. Results: 109 patient episodes were reviewed. 14 had no evidence of UGIB and were excluded from further analysis. 59 (76.6%) of patients had an initial risk assessment (including documented score) completed on admission. After excluding patients with major non-medical ('social') issues, 53 (69%) GI and 24 non-GI patients were compared. The two groups were broadly similar in their baseline characteristics. Mean length of stay (days) was significantly shorter in the GI group: 5.5 ± 5.7 vs 15.7 ± 20.8 (p = 0.02). Other comparators are shown in the table. Conclusion: The length of stay of patients with UGIB is dramatically shorter when receiving specialist care. This was statistically significant even after adjusting for social issues. Further data regarding the specific management of each case will be forthcoming. In line with previous reports [3], we found that the incidence of UGIB was higher in males. There was a trend toward better risk assessment, shorter time to endoscopy, reduced need for surgery and mortality in the GI group. Mortality rates in both groups compared favourably to the national average. Disclosure of Interest: None Declared References: CG141 Scope for improvement: A toolkit for a safer Upper Gastrointestinal Bleeding (UGIB) service. www.bsg.org.uk Lanas A, García-Rodríguez LA, Polo-Tomás M etal; Am J Gastroenterol 2009; 104:1633–41.